Loneliness over a Piece of Paper. Maria Dąbrowska as an Epistolographer - Głębicka, Ewa (Tematy i Konteksty, 2021)
The article discusses Maria Dąbrowska’s vast correspondence, which complete, in a way, her Dzienniki [Journals] , constituting very valuable biographical material, so far published only in selected fragments. Among many of her sets of letters, the most interesting ones are those exchanged with her husband, Marian Dąbrowski, her partner, Stanisław Stempowski, and later on with his son, Jerzy, as well as with her very close friend and partner, Anna Kowalska. This article discusses the most important sets of letters from and to Dąbrowska, indicating their historical value and biographical significance.